Conflict of Interest at Microsurgery Conferences: Disclosure of Its Extent and Nature - Ha, Grace; Gray, Rachel; Clappier, Mona; Tanna, Neil; Kasabian, Armen K. (Journal of Reconstructive Microsurgery, 2021)
Background Industry relationships and conflicts of interest can impact research funding, topics, and outcomes. Little research regarding the role of biomedical companies at microsurgery conferences is available. This study evaluates the role of industry at conferences by comparing payments received by speakers at the American Society for Reconstructive Microsurgeons (ASRM) meeting with those received by speakers at the American Society of Aesthetic Plastic Surgeons (ASAPS) meeting, the American Society of Plastic Surgeons (ASPS) meeting, and an average plastic surgeon. It also compares payments made by different companies.Methods General payments received by speakers at the 2017 ASAPS, ASPS, and ASRM conferences were collected from the Open Payments Database. Mean payments received at each conference were calculated and the Mann–Whitney U test evaluated differences between conference speakers and the average plastic surgeon. The total amount of payments from each company was collected through the Open Payments Database, and Z-tests identified which companies paid significantly more than others.Results The mean (and median) general payments made to conference speakers at ASAPS (n = 75), ASPS (n = 247), and ASRM (n = 121) were $75,577 ($861), $27,562 ($1,021), and $16,725 ($652), respectively. These payments were significantly greater (p < 0.001 for all) than those of the average plastic surgeon ($4,441 and $327), but not significantly different from each other. Allergan contributed significantly more than other companies to speakers at ASPS and ASAPS, while LifeCell Corporation, Zimmer Biomet Holdings, and Axogen contributed significantly more to speakers at ASRM.Conclusion Payments to physicians at ASRM were significantly higher than those of an average plastic surgeon but not significantly different from those of speakers at ASAPS and ASPS. Certain companies paid significantly more than their peers at each conference. Given these findings, speakers should strive to make clear the nature and extent of their conflicts of interest when presenting at conferences.
Keywords: conflict of interest; conferences; microsurgery